Pengaruh PjBL Terintegrasi Kearifan Lokal Tri Hita Karana untuk Meningkatkan Keterampilan Berkolaborasi Siswa Sekolah Dasar - Sanjaya, I W. Heru; Lasmawan, I Wayan; Kertih, I Wayan (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to analyze the influence of the Integrated Project-Based Learning (PjBL) model incorporating Tri Hita Karana, a Balinese local wisdom, in enhancing collaborative skills in elementary school social studies learning.Method – This research employs an experimental method with a quasi-experimental design, specifically a post-test control group design. The study population comprises students from SD Gugus Kapten Japa, Denpasar City, Bali Province. The sample was selected using a random sampling technique, with SD N 22 Dauh Puri serving as the control group and SD N 17 Dauh Puri as the experimental group. Data were collected using a collaboration skills questionnaire based on a four-point scale. Findings – The study results, based on a t-test analysis, indicate a significance value of 0.001 (<0.05), suggesting a significant influence of the Tri Hita Karana-integrated PjBL model on students' collaborative skills. This confirms that integrating local wisdom into PjBL enhances students' ability to collaborate effectively. Research Implications – By incorporating Tri Hita Karana into the PjBL model, learning activities become more engaging and foster harmony despite differences, ultimately improving students' collaborative skills while preserving local wisdom. Future research is encouraged to explore other innovative learning models that integrate local wisdom to further enhance 21st-century skills and cultural responsiveness.